3D network super-hydrophobic hexafluorbisphenol A poly(aryl ether ketone) membrane prepared by one-step electrospraying. (December 2020) - Wang, Yongpeng; Yan, Pengtao; Huo, Xintong; Liu, Mengzhu; Zhang, Haibo; Jiang, Zhenhua
Novel super-hydrophobic poly(aryl ether ketone) (PAEK) membranes have been firstly prepared by modifying ordinary PAEK into hexafluorbisphenol A-PAEK through traditional nucleophilic condensation polymerization and subsequently simple electrospraying technique. With the solution concentration increased, the micromorphology exhibited nanofibers, nanofiber with spindles, 3D network with microspheres embedded, microspheres and dense films, successively. The static water contact angle increased from 99° to 155°, while the sliding angle from 1.3° to 6.8° (±1°), in which the 3D network presented the strongest super-hydrophobicity. After 200 h of water flushing, the rough surface structure and super-hydrophobicity of the membranes were well retained. Moreover, the membrane exhibited wonderful self-cleaning property, oil/water separation property, and stability due to the hierarchical micro/nanostructures. This work provides a new route for the creation of super-hydrophobic high performance engineering plastic fabrics with the potential values in large-scale application of filtration, oil/water separation, and antifouling.